Effect of the ABCDE bundle on the risk of complications in patients undergoing mechanical ventilation - Javad Malekzadeh; Mahsa Quchani; Ahmad Bagheri Moghadam; Tahereh Sadeghi; Mohammad Rajabpour (Tehran University of Medical Sciences, 2024)
Background & Aim: With advancements in treatment and an increase in the prevalence of diseases, the number of patients requiring mechanical ventilation in intensive care units (ICUs) continues to rise each year. The ABCDE bundle is a multi-component, evidence-based approach designed to improve patient outcomes in the ICU. This study aimed to determine the effect of the ABCDE bundle on the risk of pressure ulcers, deep vein thrombosis and delirium in patients undergoing mechanical ventilation. Methods & Materials: This randomized, single-blind clinical trial was conducted between September 2021 and January 2022. The sample included 100 patients undergoing mechanical ventilation in the ICU department of Imam Reza Hospital in Mashhad, who were randomly assigned to either the intervention or control group using block randomization. The intervention group received the ABCDE bundle over a period of 7 days. The control group received routine care. The criteria for assessing complications included the risk of pressure ulcers and deep vein thrombosis (DVT), evaluated at the end of the intervention and on days 0, 1, 3, 5, and 7. The study utilized several assessment tools: the COMHON Index for pressure ulcers, the Wells Deep Vein Thrombosis Scale, and the Delirium Evaluation Tool in the Intensive Care Unit (CAM-ICU). Data analysis was performed using SPSS software version 20, employing chi-square, Mann-Whitney, and independent t-tests. Results: A decrease in the average pressure ulcer risk score was observed in the intervention group on day seven (P<0.05). In this group, the incidence of delirium fell decreased from 64.4% to 13.3% (P<0.05), indicating a statistically significant reduction. Additionally, the risk score for deep vein thrombosis in the control group significantly increased on day seven compared to the intervention group (P<0.05). Conclusion: The use of the ABCDE bundle significantly reduces the risk of pressure ulcers, deep vein thrombosis, and delirium in patients undergoing mechanical ventilation and represents an effective strategy that can be implemented by nurses and other trained healthcare professionals. Clinical trial registry: IRCT20190625044000N1